Expansion RTPA specification for representing domain analysis - Мендзебровський, Ігор Борисович; Сидоров, Євген Миколайович; Дуднік, Валентин Володимирович (Ukrainian Information Security Research Journal, 2012)
In article the problem of automating process executing domain analysis in software development is looked. Extending formal specifications means RTPA is fulfilled.